1985
DOI: 10.1067/mva.1985.avs0020015
|View full text |Cite
|
Sign up to set email alerts
|

The role of carotid duplex scanning in surgical decision making

Abstract: Eighty-one patients suspected of having cerebrovascular disease had 157 carotid arterial systems studied by both duplex ultrasonography and contrast arteriography to better define the role of carotid duplex scanning in the surgical decision-making process. These studies were reviewed in a blinded fashion in conjunction with history and physical examination data by two surgeons, one operating on only symptomatic lesions, the other operating on both symptomatic and asymptomatic lesions. Results were analyzed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Nearly all of the previous ultrasound criteria not based on these endarterectomy trials have been gradually discarded. 6,[18][19][20][21][22][23][24] Among the new ultrasound criteria, absolute Doppler velocity criteria proved the most promising for the detection of threshold carotid stenoses. [6][7][8] However, criteria were quite divergent among these studies and some of their study methods are still being debated.…”
Section: Figmentioning
confidence: 99%
“…Nearly all of the previous ultrasound criteria not based on these endarterectomy trials have been gradually discarded. 6,[18][19][20][21][22][23][24] Among the new ultrasound criteria, absolute Doppler velocity criteria proved the most promising for the detection of threshold carotid stenoses. [6][7][8] However, criteria were quite divergent among these studies and some of their study methods are still being debated.…”
Section: Figmentioning
confidence: 99%
“…3 The accuracy of duplex ultrasound scanning in evaluating carotid artery disease has been reported as having sensitivity of 99% and specificity of 84%. 5,6 We sought to review the natural history of disease progression in the contralateral carotid artery in patients who underwent CEA and were surveilled with duplex ultrasound scanning; imaging of both carotid arteries was performed at each visit. This allowed us to study both disease progression in the contralateral carotid artery and recurrent stenosis in the ipsilateral carotid artery.…”
mentioning
confidence: 99%
“…We mention digital subtraction angiography (DSA) first because it is the test by which all others are measured. [4][5][6][7][8][9][10][11][12][13] Prior to the advent of newer techniques, conventional angiography was the test of choice for most neck vessel and cerebral pathology. 14 The majority of the early work in conventional angiography was completed by Egas Moniz as early as 1927.…”
Section: Digital Subtraction Angiographymentioning
confidence: 99%
“…Flanigan et al, in a blinded study of 157 carotid artery systems, compared the relative accuracies of carotid DUS with contrast arteriography. 6 They showed that, relative to arteriography, DUS was 81% accurate in the detection of disease, 83% accurate in the detection of critical stenosis, 90% accurate in the detection of ulceration, and 99% accurate in the detection of complete occlusion. They concluded that DUS was capable of providing accurate information for surgical decision making in a high percentage of patients, with limited application of arteriography when insufficient information is present.…”
Section: Carotid Duplex Ultrasonographymentioning
confidence: 99%